Transcriptomic Analysis Reveals Molecular Mechanisms Underpinning Mycovirus-Mediated Hypervirulence in Beauveria bassiana Infecting Tenebrio molitor - Charalampos Filippou; Robert H. A. Coutts; Ioly Kotta-Loizou; Sam El-Kamand; Alexie Papanicolaou (Journal of Fungi)
Mycoviral infection can either be asymptomatic or have marked effects on fungal hosts, influencing them either positively or negatively. To fully understand the effects of mycovirus infection on the fungal host, transcriptomic profiling of four Beauveria bassiana isolates, including EABb 92/11-Dm that harbors mycoviruses, was performed 48 h following infection of Tenebrio molitor via topical application or injection. Genes that participate in carbohydrate assimilation and transportation, and those essential for fungal survival and oxidative stress tolerance, calcium uptake, and iron uptake, were found to be overexpressed in the virus-infected isolate during the mid-infection stage. Mycotoxin genes encoding bassianolide and oosporein were switched off in all isolates. However, beauvericin, a mycotoxin capable of inducing oxidative stress at the molecular level, was expressed in all four isolates, indicating an important contribution to virulence against T. molitor. These observations suggest that detoxification of immune-related (oxidative) defenses and nutrient scouting, as mediated by these genes, occurs in mid-infection during the internal growth phase. Consequently, we observe a symbiotic relationship between mycovirus and fungus that does not afflict the host; on the contrary, it enhances the expression of key genes leading to a mycovirus-mediated hypervirulence effect.